Boosting the Limited Use of Mineralocorticoid Receptor Antagonists Through New Agents for Hyperkalemia - Athyros, Vasilios G.; Sachinidis, Alexandros G.; Zografou, Ioanna; Simoulidou, Elisavet; Piperidou, Alexia; Stavropoulos, Nikiforos; Karagiannis, Asterios (Current Pharmaceutical Design, 2018)
Background: Hyperkalemia is an important clinical problem that is associated with significant lifethreatening complications. Several conditions are associated with increased risk for hyperkalemia such as chronic kidney disease, diabetes mellitus, heart failure, and the use of renin-angiotensin-aldosterone system (RAAS) inhibitors. Objective: The purpose of this review is to present and critically discuss treatment options for the management of hyperkalemia. Method: A comprehensive review of the literature was performed to identify studies assessing the drug-induced management of hyperkalemia. Results: The management of chronic hyperkalemia seems to be challenging and includes a variety of traditional interventions, such as restriction in the intake of the dietary potassium, loop diuretics or sodium polystyrene sulfonate. In the last few years, several new agents have emerged as promising options to reduce potassium levels in hyperkalemic patients. Patiromer and sodium zirconium cyclosilicate 9 (ZS-9) have been examined in hyperkalemic patients and were found to be efficient and safe. Importantly, the efficacy of these novel drugs might allow the continuation of the use of RAAS inhibitors, morbidity- and mortality-wise beneficial class of drugs in the setting of chronic kidney disease and heart failure. Conclusion: Data support that the recently emerged patiromer and ZS-9 offer significant hyperkalemia-related benefits. Larger trials are needed to unveil the impact of these drugs in other patients’ subpopulations, as well.
Keywords: sodium polystyrene sulfonate